(untitled) (Kathmandu University Medical Journal, 2012)
Background Leprosy is a chronic, infectious disease caused by Mycobacterium leprae. It is classified into five groups based on clinical, histological, microbiological and immunological criteria (Ridley & Jopling Classification). However, a great variation has been observed in the interpretation of histopathological examination ok skin biopsies and clinical presentation of the disease. Objective To correlate clinical diagnosis with histopathological diagnosis of leprosy patients in Nepal. Methods A retrospective hospital-based study was conducted among patients with all clinical types of leprosy, classified as per the Ridley-Jopling classification. Skin biopsies were taken from active lesions in all patients and were stained with Hematoxylin & Eosin stain and modified Fite-Ferraco stain for identification of Mycobacterium leprae. The histopathological findings were compared with clinical diagnoses. Results A total 156 patients were studied, out of which 84 (53.8%) males and 72 (46.1%) females between 8 and 86 years of age. The majority of patients 33 (23.57%) were in the age group of 21-30 years and least affected was children below 10 years 1(0.007%).Overall coincidence of clinical and histopathological diagnoses of classification was seen in 115 cases (80.4%). The maximum correlation (95.2%) was noted in LL patients (p value 0.000049) followed by BT(89.74%), TT (73.2%), BL(72.4%), BB(64.7%). Conclusion Leprosy still continues to be one of the common infectious disease in Nepal and skin biopsy is a useful tool in confirming the clinical diagnosis of leprosy as well as for the therapeutic guide. DOI: http://dx.doi.org/10.3126/kumj.v9i4.6338 Kathmandu Univ Med J 2011;9(4):248-51